Pengaruh Penggunaan Media Pembelajaran Monoculture (Monopoly Culture) Terhadap Pemahaman Siswa Kelas V - Elwarin, Wisje Krensia; Yohanes, Nathalia Yohanna; Mahananingtyas, Elsinora (Universitas Garut, 2025)
This study aims to examine the effect of using the monoculture (Monopoly Culture) learning media on the understanding of Maluku cultural heritage material among fifth-grade students at SD Negeri 1 Lateri in the subject of Social Science and Natural Science (IPAS). The IPAS learning process, which tends to be less interactive and limited to discussion-based methods, is one of the factors affecting students' understanding of the material. Therefore, a game-based learning media, modified with local cultural values, is expected to enhance student engagement and understanding. This study employs a quantitative approach with a Pre-Experimental One Group Pretest and Posttest design. The results show that the use of monoculture media significantly improves students' understanding. The Paired Sample t-Test results revealed a significant difference between the pretest and posttest scores with a significance value of 0.000 (< 0.05). Furthermore, the N-Gain calculation yielded a mean value of 0.8007, indicating a high level of effectiveness in improving students' understanding of the cultural material. The Monoculture media serves not only as an enjoyable learning tool but also supports the introduction and reinforcement of local cultural values within the learning context. This study confirms that game-based learning that integrates local culture can improve learning outcomes and student engagement.